Oxford case histories in infectious diseases and microbiology - Humphreys, Hilary; Irving, William L.; Atkins, Bridget; Woodhouse, Andrew (Oxford : Oxford University Press, 2020)
Part of the Oxford Case Histories series, this volume contains over 45 well-structured cases from clinical practice, giving a comprehensive coverage of the diagnostic and management dilemmas faced in clinical microbiology and infectious diseases.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 27, 2020).
Keywords: Communicable diseases; Infection; Medical microbiology